The study of geometric forms, proportion and scale of heritage buildings due to architectural theory - Eva Evita Chatharina Josephine (Institut Teknologi Sepuluh Nopember, 2017)
Architecture is the shapes of structure and enclosure that occurs from the elements of space organization patterns, space relationships and hierarchy, geometric shapes, scale ratio and proportion. In addition, architecture is the places of the programs from user requirements, user needs and aspirations, economic and social factors, cultural factor, the legality and the historical. Hence, from the building architectural styles,we could notify the history and the culture developments of a region. For example, Jakarta as a city has many buildings with different kinds of architectural style which is varies according to the years or times when the building was erected. To get further, in Central Jakarta, there are many kinds of historical and monumental buildings. Thus, in this study, we choose the historical and monumental buildings types such as the Elephant Museum which is in the Dutch Colonial Architecture style, the Istiqlal Mosque which is in Modern Islamic Architecture style, the National Monument Building which is in Modern Architecture style, and the Cathedral Church which is in Neo-Gothic Architecture style. We use geometric operation methods to studying the form suitability with the spaces function and the golden section method to find the scale ratio and proportion of the building facades. The result of this research finds that when the aesthetic value of edifices conforms the architectural theory rules, it could produces a good design.